The Theory of Fusion Systems : An Algebraic Approach / [electronic resource] - Craven, David A. (Cambridge : Cambridge University Press, 2011)
Fusion systems are a recent development in finite group theory and sit at the intersection of algebra and topology. This book is the first to deal comprehensively with this new and expanding field, taking the reader from the basics of the theory right to the state of the art. Three motivational chapters, indicating the interaction of fusion and fusion systems in group theory, representation theory and topology are followed by six chapters that explore the theory of fusion systems themselves. Starting with the basic definitions, the topics covered include: weakly normal and normal subsystems; morphisms and quotients; saturation theorems; results about control of fusion; and the local theory of fusion systems. At the end there is also a discussion of exotic fusion systems. Designed for use as a text and reference work, this book is suitable for graduate students and experts alike.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Finite groups; Representations of algebras; Algebraic topology